2013
DOI: 10.1002/jmor.20120
|View full text |Cite
|
Sign up to set email alerts
|

Conservation of placentation during the tertiary radiation of mammals in South America

Abstract: The eutherian placenta is considered to possess great plasticity, but it is not clear how this variation reflects adaptation to different ecological niches. Because South America was isolated for most of the Tertiary, it represents a natural laboratory to examine this question. We here describe placentation in three South American groups: Xenarthra have been part of the fauna from at least the mid-Paleocene whereas caviomorph rodents and Neotropical primates are each derived from a single founder that reached … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 91 publications
0
14
0
Order By: Relevance
“…Most of these features exhibit parallels to humans [119]. In humans the syncytiotrophoblast is formed from proliferative cytotrophoblast cells and we have suggested that the cytotrophoblast cells in xenarthran species have a similar function [52]. However, the villous pattern in anteaters (giant anteater Myrmecophaga tridactyla, lesser anteater Tamandua tetradactyla, and two-toed anteater Cyclopes didactyla) is much simpler in terms of developmental differentiation and more similar to humans than the condition in armadillos.…”
Section: Xenarthramentioning
confidence: 80%
See 4 more Smart Citations
“…Most of these features exhibit parallels to humans [119]. In humans the syncytiotrophoblast is formed from proliferative cytotrophoblast cells and we have suggested that the cytotrophoblast cells in xenarthran species have a similar function [52]. However, the villous pattern in anteaters (giant anteater Myrmecophaga tridactyla, lesser anteater Tamandua tetradactyla, and two-toed anteater Cyclopes didactyla) is much simpler in terms of developmental differentiation and more similar to humans than the condition in armadillos.…”
Section: Xenarthramentioning
confidence: 80%
“…Among 2 Advances in Biology them are nonmurine rodents native to South America and Africa [26][27][28][29][30][31][32][33][34][35][36][37][38][39][40], as was shown by Figure 2, bats [41][42][43], anteaters and armadillos [44,45], and some other taxa [46][47][48][49][50][51]. Also, there were several promising attempts to reinvestigate historical histological material from museum collections such as neotropical primates [52] or great apes [53][54][55][56] in order to answer open questions.…”
Section: Comparative Placentationmentioning
confidence: 99%
See 3 more Smart Citations